1733. 10 Years of DTAC Experience With Donor-Derived Cryptococcus Transmission in Solid-Organ Transplantation in the United States. (26th November 2018) - Mehta, Aneesh K; Malinis, Maricar; Vece, Gabriel; Danziger-Isakov, Lara; Florescu, Diana F; Michaels, Marian; Wolfe, Cameron R; Strasfeld, Lynne; Tlusty, Susan
Abstract: Background: Cryptococcosis is an important fungal complication of solid organ transplantation (SOT); cases occurring within 6 months posttransplant are often severe and sometimes donor derived. Morbidity can be related to delayed recognition of clinical symptoms or lack of communications among the SOT recipient centers. To better understand transmission of Cryptococcus (Crypto) and to identify opportunities for improved identification and communication, all potential donor-derived transmission events (PDDTE) of Crypto reported to OPTN/UNOS ad hoc Disease Transmission Advisory Committee (DTAC) over 10 years were analyzed. Methods: All Crypto cases reported to DTAC between January 2008 and December 2017 were reviewed retrospectively as potential donor-derived transmission events (PDDTE). Likelihood of donor-derivation was adjudicated based on recipient and donor data. Results: Fourty-six cases of Crypto were reported to DTAC during this period, involving 145 SOT recipients. Of the Proven or Probable donor-derived Crypto cases ( n = 9), transmission occurred in 15 recipients; 2 donors each transmitted Crypto to 3 different recipients. Of the Possible cases, 9 recipients were affected. Six recipients with PDDTE Crypto died. Eight recipients received antifungal medications that would prevent transmission of Crypto (classified as intervention without disease transmission). UNOS Region 7 had the highest number donors with 10, with 6 and 7 from Regions 2 and 3, respectively. No cases C. gattii were reported; however, most of the reports to DTAC did not discriminate between C. neoformans and C. gattii . Conclusion: This DTAC case series highlights both donor and recipient-derived cryptococcal infections and their potential to have devastating clinical impact. These data also highlight important delays in recognizing Crypto in SOT and in communicating these results to other centers when a PDDTE is possible. Transplant teams should have a high level of suspicion for Crypto in SOT, particularly in those with fever of unknown etiology, pulmonary infiltrates, headaches, and mental status changes. In the future, it may be helpful for transplant center to perform specific testing to discriminate between Cryptococcus species to understand their differential impact in SOT. Disclosures: D. F. Florescu, Astellas: Grant Investigator, Grant recipient. C. R. Wolfe, Merck: Scientific Advisor, Consulting fee.